Immobilization of Copper and Fluoride in Soils: Uptake by Chinese Cabbage - Yasin Senkondo; Stalin Mkumbo; Paula Sospeter (Bulgarian Journal of Soil Science)
Elevated concentrations of fluoride (F) and copper (Cu) in food substances cause health problems. Effects of Wood ash, Cattle manure and CAN+NPK on mobility and uptake of Cu and F by Chinese cabbage were explored. The soils in this study were collected from Arusha, Tanzania. The experiment was completely randomized design with four treatments, each replicated four times. Four Chinese cabbage seeds were sown in the sieved soil samples (1 kg) and sown in 1 L containers. The Chinese cabbage were irrigated daily and allowed to grow for six weeks, and harvested. Organic amendments decreased the soluble fractions of Cu and F in the soils and reduced their uptake by Chinese cabbage. For fluoride, although significant reductions were observed, the concentrations were still above the allowed concentrations for human consumption. The Wood ash treatment was generally the most effective treatment of all. It was revealed that log10 of Cu concentrations in Chinese cabbage was positively related with log10 concentration of F in the plants, elucidating that the presence of one contaminant will generally enhance the uptake of the other. It was concluded that the amendments reduced the possibility of contaminating the food chain by the two pollutants in the soils.